EFEK POTENSIAL SOAL PENALARAN TIPE TIMSS MENGGUNAKAN KONTEKS BUDAYA LAMPUNG - Tri Wahyudi (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2017)
The results of the TIMSS study show that Indonesia's rank in mathematics is still low, especially in the cognitive domain of reasoning. This is due to Indonesian students are less accustomed to solve math problems that have a high complexity which demands reasoning skills such as TIMSS problem. The use of context in the exercise of mathematical problems is exactly precise because it is useful in the formation of concepts, access and motivation towards mathematics, modeling, providing tools for thinking using procedures, notations, drawings and rules, reality as the source and application domain, and specific skills training In certain situations. One of contexts that can be used is culture. Mathematics in essence grows from the skill or activity of the cultural environment, so that the mathematics of a person is influenced by his cultural background. This study aims to see the potential effects generated by the problem of specially designed reasoning with the TIMSS problem and using the Lampung cultural context. From the results of the research shows the problems are able to attract interest, motivate and foster the seriousness of students to solve the problem. In addition, these problems are able to elicit students' mathematical reasoning skills, lure students to think harder, more thoroughly, and reason using logic in solving problems.